Enduring the Loneliness inside the Catholic Diocesan College Seminary - Genesis B. Naparan; Seminarian Clive Jarry S. Kingco; Seminarian Arnel G. Bolivar; Seminarian Ralph Kenneth S. Salinas (Budapest International Research and Critics University, 2020)
Seminarians inside the Seminary experienced many difficulties. One of them is the experience of loneliness. The present research examined the ways of enduring the loneliness inside the Seminary. The purpose of this study is to help improve the commitment in the priesthood. The researchers used a qualitative transcendental phenomenological approach in exploring the experiences of nine college seminarians. Phenomenological is an approach to qualitative research that describes the meaning of several individuals' lived experiences, which in this research talks about the seminarians' loneliness inside the Seminary. The forms of loneliness experienced by the seminarians are classified into three themes: 1) Seminary-Related Loneliness; 2) Living away from the family, and 3) Being alone. The seminarians deal with their experienced loneliness through Social Interaction, Prayer, and making the Self Busy. The results reveal that loneliness inside, although inevitable, can be prevented through prevention measures. Future researchers may conduct a further study on how to improve the seminarians' lives inside the Seminary to help the seminarians be more committed to the priesthood.